Influence of Physical and Psychological of Pregnant Women Toward Health Status of Mother and Baby - Alfiah Rahmawati; Rr Catur Leny Wulandari (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
Pregnancy is a natural event for women, a woman will experience changes in him both physically and psychologically. The two problems we face very often are the field of psychology of pregnant women is the feeling of fear and rejection of pregnancy. Physically there will be an enlargement of the abdomen, felt the movement / emergence of hyperpigmentation, the release of colostrum and anxiety. This feeling of fear and anxiety will arise in primiparous and multiparous pregnant women who are having a pregnancy. The purpose of this study was to determine the effect of physical and psychological readiness of third trimester pregnant women on the welfare of the mother and fetus. This study was an observational analytic study using a cross-sectional study design. Independent variables are age, education, marital status, parity. The dependent variable is the incidence of pre-eclampsia. Accidental sampling technique. This research was conducted in Rusunawa Kaligawe Semarang. Bivariate data analysis uses chi square test. The results showed that physical and psychological readiness variables were not related to maternal well-being with a p value of 0.369 (p value 0.05). Variable physical and psychological readiness associated with fetal well-being with a p value of 0.018 (p value 0.05). The conclusion is a statistically significant positive relationship between physical and psychological readiness of pregnant women and fetal well-being in Rusunawa Kaligawe Semarang City and there is no positive and statistically significant relationship between physical and psychological readiness of pregnant women towards maternal welfare.